Immunomodulatory effects of oak dust exposure in a murine model of allergic asthma. - Määttä, J; Haapakoski, R; Lehto, M; Leino, M; Tillander, S; Husgafvel-Pursiainen, K; Wolff, H; Savolainen, K; Alenius, H (2007)
Repeated airway exposure to wood dust has been reported to cause adverse respiratory effects such as asthma and chronic bronchitis. In our recent study, we found that exposure of mice to oak dust induced more vigorous lung inflammation compared to birch dust exposure. In the present study, we assessed the immunomodulatory effects of repeated intranasal exposure to oak dust both in nonallergic and in ovalbumin-sensitized, allergic mice. Allergen-induced influx of eosinophils and lymphocytes was seen in the lungs of allergic mice. Oak dust exposure elicited infiltration of neutrophils, lymphocytes, and macrophages in nonallergic mice. Interestingly, oak dust-induced lung neutrophilia as well as oak dust-induced production of the proinflammatory cytokine TNF-alpha and chemokine CCL3 were significantly suppressed in allergic mice. On the other hand, allergen-induced expression of IL-13 mRNA and protein was significantly reduced in oak dust-exposed allergic mice. Finally, allergen-induced airway hyperreactivity to inhaled metacholine was significantly suppressed in oak dust-exposed allergic mice. The present results suggest that repeated airway exposure to oak dust can regulate pulmonary inflammation and airway responses depending on the immunological status of the animal.